2023
DOI: 10.1159/000530650
|View full text |Cite
|
Sign up to set email alerts
|

The Importance of Symptom Reduction for Functional Improvement after Cognitive Behavioral Therapy for Anxiety and Depression: A Causal Mediation Analysis

Abstract: <b><i>Introduction:</i></b> The temporal relationship between symptoms and functioning in the context of cognitive behavioral therapy (CBT) for anxiety and depression is not fully understood, and there are few high-quality studies that have examined to what extent late intervention effects of CBT on functioning are mediated by initial intervention effects on symptoms while accounting for the initial effects on functioning and vice versa. <b><i>Objective:</i></b> … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 48 publications
(76 reference statements)
0
1
0
Order By: Relevance
“…To illustrate this, we surveyed all 2022 and 2023 issues of Psychotherapy and Psychosomatics which ranks among the highest-impact psychology journals (Impact Factor 2023: 26.617). We found that of 17 studies that reported results of regression analyses [22][23][24][25][26][27][28][29][30][31][32][33][34][35][36][37][38], only six made use of at least one of these visualizations [22][23][24][25][26][27]. One of them applied a forest plot variant [22].…”
Section: Reporting and Visualizing Regression Modelsmentioning
confidence: 99%
“…To illustrate this, we surveyed all 2022 and 2023 issues of Psychotherapy and Psychosomatics which ranks among the highest-impact psychology journals (Impact Factor 2023: 26.617). We found that of 17 studies that reported results of regression analyses [22][23][24][25][26][27][28][29][30][31][32][33][34][35][36][37][38], only six made use of at least one of these visualizations [22][23][24][25][26][27]. One of them applied a forest plot variant [22].…”
Section: Reporting and Visualizing Regression Modelsmentioning
confidence: 99%